EFFECT OF SOWING DATE, IRRIGATION REGIME AND MINERAL FERTILIZER RATE ON GRAIN YIELD OF WINTER WHEAT VARIETIES IN SOIL CONDITIONS OF DESERT REGION - Yodgorov N.G.; Khalikov B.M.; Azizov B.M. (Journals Park Publishing, 2023)
In this article, in the conditions of the barren soils of the desert region of Kashkadarya region, in 2015-2017, the varieties of winter wheat "Zimnitsa" and "Gozgon" were planted in the periods 01-05.10 and 15-20.10, and in their cultivation 70-75-60 and 75-80-70% compared to LFWC irrigation procedures and NPK of mineral fertilizers 100:75:50; The norms of 180:120:90 and 250:175:125 kg/ha, in the conditions of light sierozem soils of the desert region, in the maintenance of winter wheat varieties "Alekseeich", "Bunyodkor" and "Shams" in 2020-2022 compared to LFWC 70-70-60 and 75-80-70% irrigation procedures and NPK of mineral fertilizers- 120:80:60; The analysis of the scientific data obtained on the effect of winter wheat varieties on grain yield when using the norms of 180:120:90 and 240:160:120 kg/ha is presented.
Keywords: soil, climate, region, winter wheat, variety, sowing, date, rate, fertilization, irrigation, grain, harvest.